Kuasa Simbolik Perspektif Pierre Bourdieu dalam Pembelajaran Sastra Perguruan Tinggi - Panji Kuncoro Hadi; Bambang Eko Hari Cahyono; Dwi Rohman Soleh (Balai Bahasa Provinsi Bali, 2026)
The development of literature learning in higher education cannot be separated from the influence of aesthetic ideology that shapes how students understand and write literary works. This study examines symbolic power from Pierre Bourdieu’s perspective in literature learning at the university level. The research problem focuses on the internalization of universal humanist literature in students’ poetry through literature instruction. This study aims to describe the forms of symbolic power that influence the themes, diction, and language styles of students’ poetry. The method employed is descriptive qualitative, with data consisting of 30 student poems from poetry appreciation and poetry studies courses. The data were analyzed using Pierre Bourdieu’s theory of symbolic power through thematic analysis, word choice, and language style. The findings reveal that literature learning in higher education tends to internalize the aesthetics of universal humanist literature among students. Of the 30 poems analyzed, most demonstrate uniformity in themes, poetic diction, and the use of language styles that represent the dominance of legitimate aesthetics. This condition indicates the presence of symbolic power in literature learning that shapes students’ perceptions of poetic standards. This study recommends a literature learning approach that is more open to the diversity of students’ social experiences and habitus so that literary creativity can develop more authentically. AbstrakPerkembangan pembelajaran sastra di perguruan tinggi tidak terlepas dari pengaruh ideologi estetika yang membentuk cara mahasiswa memahami dan menulis karya sastra. Penelitian ini membahas kuasa simbolik perspektif Pierre Bourdieu dalam pembelajaran sastra di perguruan tinggi. Permasalahan penelitian difokuskan pada internalisasi sastra humanis universal dalam puisi mahasiswa melalui pembelajaran sastra. Penelitian ini bertujuan mendeskripsikan bentuk kuasa simbolik yang memengaruhi tema, diksi, dan gaya bahasa puisi mahasiswa. Metode yang digunakan adalah deskriptif kualitatif dengan data berupa 30 puisi mahasiswa pada mata kuliah apresiasi dan kajian puisi. Data dianalisis menggunakan teori kuasa simbolik Pierre Bourdieu melalui analisis tema, pilihan kata, dan gaya bahasa. Hasil penelitian menunjukkan bahwa pembelajaran sastra di perguruan tinggi cenderung menginternalisasikan estetika sastra humanis universal kepada mahasiswa. Dari 30 puisi yang dianalisis, sebagian besar menunjukkan keseragaman tema, diksi puitis, dan penggunaan gaya bahasa yang merepresentasikan dominasi estetika legitim. Kondisi tersebut menunjukkan adanya kuasa simbolik dalam pembelajaran sastra yang membentuk persepsi mahasiswa mengenai standar kepuitisan. Penelitian ini merekomendasikan pembelajaran sastra yang lebih terbuka terhadap keberagaman pengalaman sosial dan habitus mahasiswa agar kreativitas sastra berkembang secara lebih autentik.